Reallocating Public Spending to Reduce Income Inequality : Can It Work? - Doumbia, Djeneba (IMF Working Papers; Working Paper, 2019)
Can a government reduce income inequality by changing the composition of public spending while keeping the total level of expenditure fixed? Using newly assembled data on spending composition for 83 countries across all income groups, this paper shows that reallocating spending toward social protection and infrastructure is associated with reduced income inequality, particularly when it is financed through cuts in defense spending. However, the political and security situation matters. The analysis does not find evidence that lowering defense spending to finance infrastructure and social outlays improves income distribution in countries with weak institutions and at higher risk of conflict. Reallocating social protection and infrastructure spending towards other types of spending tends to increase income inequality. Accounting for the long-term impact of health spending, and particularly education spending, helps to better capture the equalizing effects of these expenditures. The paper includes a discussion of the implications of the findings for Indonesia, a major emerging market where income inequality is at the center of policy issues.